Preoperative statin therapy and infectious complications in cardiac surgery - Hartholt, N. L. (Neth Heart J, 2014)
AIM: To assess whether preoperative statin therapy is associated with the risk of postoperative infection in patients undergoing cardiac surgery. METHODS: 520 patients undergoing cardiac surgery in 2010 were retrospectively examined. Data regarding statin and antibiotic use prior to and after surgery were available from the hospital pharmacy information system. Cultures and clinical data of patients on postoperative antibiotics other than standard prophylactic therapy were studied to identify postoperative infections up to 30 days from day of surgery. RESULTS: 370 (71.2 %) patients were on preoperative statin therapy. Overall, 82 patients (15.8 %) suffered from postoperative infection of which 11 were surgical site infections. In multivariable regression analysis, statin therapy was associated with a reduced risk of postoperative infection (adjusted odds ratio: 0.329, 95 %: CI 0.19–0.57; P < 0.001). CONCLUSIONS: Preoperative statin use was associated with a considerable reduced risk of postoperative infections following cardiac surgery. Randomised controlled trials are required to clarify the role of statin therapy in the prevention of postoperative infections.